Precise tuning of facile one-pot gelatin methacryloyl (GelMA) synthesis - Shirahama, Hitomi (2018)
Gelatin-methacryloyl (GelMA) is one of the most commonly used photopolymerizable biomaterials in bio-applications. However, GelMA synthesis remains suboptimal, as its reaction parameters have not been fully investigated. The goal of this study is to establish an optimal route for effective and controllable GelMA synthesis by systematically examining reaction parameters including carbonate-bicarbonate (CB) buffer molarity, initial pH adjustment, MAA concentration, gelatin concentration, reaction temperature, and reaction time. We employed several analytical techniques in order to determine the degree of substitution (DS) and conducted detailed structural analysis of the synthesized polymer. The results enabled us to optimize GelMA synthesis, showing the optimal conditions to balance the deprotonation of amino groups with minimizing MAA hydrolysis, which led to nearly complete substitution. The optimized conditions (low feed ratio of MAA to gelatin (0.1 mL/g), 0.25 M CB buffer at pH 9, and a gelatin concentration of 10–20%) enable a simplified reaction scheme that produces GelMA with high substitution with just one-step addition of MAA in one pot. Looking forward, these optimal conditions not only enable facile one-pot GelMA synthesis but can also guide researchers to explore the efficient, high methacrylation of other biomacromolecules.